Brain Toxoplasmosis Comorbid with Autoimmune Disease: Complicated Immune Response And Case Demonstration. (July 2021) - Graham, Alice; Fong, Crystal; Naqvi, Asghar; Lu, Jian-Qiang
Abstract : Toxoplasmosis is an opportunistic infection caused by Toxoplasma gondii (TG), commonly involving the brain. Symptomatic clinical disease of TG infection is much more commonly associated with immunodeficiency; clinicopathological manifestations of brain toxoplasmosis are linked to individual immune responses including brain infiltration of T-cells that are thought to fight against toxoplasmosis. In patients with autoimmune diseases, immune status is typically characterized by T-cell infiltration and complicated mainly by immunosuppressant and/or immunomodulatory treatment. In this study, we demonstrate clinical and radiological features correlated with pathological features of brain toxoplasmosis at different disease stages in a patient with coexisting autoimmune diseases, including systemic lupus erythematosus and autoimmune hepatitis. The infiltration of CD8+ T-cells in toxoplasma immunostaining-positive acute lesions was greater than that in toxoplasma immunostaining-negative chronic lesions. We also review previously reported cases of brain toxoplasmosis with comorbid autoimmune diseases. Our present case and literature review suggest that brain toxoplasmosis in patients with autoimmune diseases may be asymptomatic unless disease complications occur; it may present as an incidental finding at postmortem examination of rapidly developed lesions. T-cell infiltration in patients with autoimmune diseases and coexisting toxoplasmosis may be at least partially reduced; ultimately, the roles of T-cell infiltration in brain toxoplasmosis deserve further investigation. Learning Objectives: Discuss complicated immune response to toxoplasmosis in patients with autoimmune diseases. Describe clinical, radiological, and pathological features of brain toxoplasmosis in patients with autoimmune diseases.